2021
DOI: 10.1038/s41598-021-82514-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using white-rot fungus Anamorphous Bjerkandera sp. R1: influence of silver nitrate concentration and fungus growth time

Abstract: Currently, silver nanoparticles (AgNPs) constitute an interesting field of study in medicine, catalysis, optics, among others. For this reason, it has been necessary to develop new methodologies that allow a more efficient production of AgNPs with better antimicrobial and biological properties. In this research growth time effects Anamorphous Bjerkandera sp. R1 and the silver nitrate (AgNO3) concentration over AgNPs synthesis were studied. Through the protocol used in this work, it was found that the action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Nanopesticides from runoff of agricultural and industrial wastewater during the precipitation event by soil permeating leaching phenomenon reach the water supply, affecting its quality, increasing the human exposure time and concerns for the ecosystem. It has been noticed that nanoparticles could cause toxicological effects by their biomimetics properties and high ability of distribution and bioaccumulation in soil, water environments, foods, and consequently in all animals, especially in mammals [3][4][5]14]. For humans, the range of side effects related to individual susceptibility and exposure time to nanoparticles leads to acute and chronic pathological manifestations that include the systems respiratory as cardiovascular, lymphatic, autoimmune, neurologic, and various cancers that can manifest instantly following exposure or many years later as a result of bioaccumulation [15] and unique nanoparticles properties [11,16,17].…”
Section: Nanopesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopesticides from runoff of agricultural and industrial wastewater during the precipitation event by soil permeating leaching phenomenon reach the water supply, affecting its quality, increasing the human exposure time and concerns for the ecosystem. It has been noticed that nanoparticles could cause toxicological effects by their biomimetics properties and high ability of distribution and bioaccumulation in soil, water environments, foods, and consequently in all animals, especially in mammals [3][4][5]14]. For humans, the range of side effects related to individual susceptibility and exposure time to nanoparticles leads to acute and chronic pathological manifestations that include the systems respiratory as cardiovascular, lymphatic, autoimmune, neurologic, and various cancers that can manifest instantly following exposure or many years later as a result of bioaccumulation [15] and unique nanoparticles properties [11,16,17].…”
Section: Nanopesticidesmentioning
confidence: 99%
“…The higher total surface area occupied by agrochemicals nanoparticulates offers overall greater contact with crop pests, making them as efficient as they are unpredictable. The unreasonable and unsystematic use of agrichemical intensifies pathogen resistance, reducing nitrogen fixation and biodiversity, and increasing bioaccumulation of pesticides in agricultural, livestock goods, and in organisms of the water environment, which poses a severe and progressive threat both to the ecosystem and to humans and an obstacle against the development of sustainable agriculture [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in comparison with other biological routes, fungi are the most attractive choice, as they secrete large amount of extracellular proteins, providing high silver nanoparticles (AgNPs) synthesis efficiency. It was also observed that fungi can withstand high pressure and agitation inside bioreactors, due to its mesh‐like fungal mycelium (Osorio‐Echavarría et al, 2021). Metallic nanoparticles have wide application in the field of pharma, textile, cosmetic, waste water treatment, food, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, chemical approaches are the most commonly used method [13][14][15] . Although chemical processes are convenient, they have a high preparation cost and negative effects to the environment; thus, it is not preferred in several research and applications [16][17][18][19][20] . Bioreduction is a novel method in preparing NS using various reducing substances or products in plants and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Bioreduction is a novel method in preparing NS using various reducing substances or products in plants and microorganisms. It has the advantages of cost-effectiveness and environmental benignity; therefore, there has been increasing interest in its research and application [19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%